COVID-19: High-JAKing of the Inflammatory “Flight” by Ruxolitinib to Avoid the Cytokine Storm - Botta, Cirino; Indrieri, Alessia; Garofalo, Eugenio; Biamonte, Flavia; Bruni, Andrea; Pasqua, Pino; Cesario, Francesco; Costanzo, Francesco Saverio; Longhini, Federico; Mendicino, Francesco (Frontiers in Oncology, 2021)
Since SARS-CoV-2 outbreak in December 2019, world health-system has been severely impacted with increased hospitalization, Intensive-Care-Unit (ICU) access and high mortality rates, mostly due to severe acute respiratory failure and multi-organ failure. Excessive and uncontrolled release of proinflammatory cytokines (cytokine-release/storm syndrome, CRS) have been linked to the development of these events. The recent advancements of immunotherapy for the treatment of hematologic and solid tumors shed light on many of the molecular mechanisms underlying this phenomenon, thus rendering desirable a multidisciplinary approach to improve COVID-19 patients’outcome. Indeed, currently available therapeutic-strategies to overcome CRS, should be urgently evaluated for their capability of reducing COVID-19 mortality. Notably, COVID-19 shares different pathogenic aspects with acute graft-versus-host-disease (aGVHD), hemophagocytic-lymphohistiocytosis (HLH), myelofibrosis and CAR-T-associated CRS. Specifically, similarly to aGVHD, an induced tissue damage (caused by the virus) leads to increased cytokine-release (TNFα and IL-6) which in turn leads to exaggerated dendritic cells, macrophages (like in HLH) and lymphocytes (as in CAR-T) activation, immune-cells migration and tissue-damage (including late-stage fibrosis, similar to myelofibrosis). Janus Kinase (JAK) signaling represents a molecular hub linking all these events, rendering JAK-inhibitors suitable to limit deleterious effects of an overwhelming inflammatory-response. Accordingly, ruxolitinib is the only selective JAK1 and JAK2-inhibitor approved for the treatment of myelofibrosis and aGVHD. Here we discuss, from a molecular and hematological point of view, the rationale for targeting JAK signaling in the management of COVID-19 patients and report the clinical results of a patient admitted to ICU among the firsts to be treated with ruxolitinib in Italy.